2020
DOI: 10.21037/apm.2020.03.10
|View full text |Cite
|
Sign up to set email alerts
|

Application of imaging technique in thoracic duct anatomy

Abstract: At 6th week of embryo development, when the embryo is about 10 mm long, the lymphatic system begins to form in the human embryo (1). At the end of the embryonic stage, 6 primary lymphatic sacs are developed in the lymphatic system including 2 cervical lymphatic sacs, 2 iliac lymphatic sacs, 1 retroperitoneal lymphatic sac and 1 cisterna chyli. Lymphatic vessels develop in a similar way to blood vessels. Lymphatic sacs are fused and reconstructed to form the original lymphatic vessels, which further develop int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…The limitation of our case study was that the anatomy of the thoracic duct before surgery was not studied due to a lack of lymphangiography. As the thoracic duct is known for frequent variation, 9 the chance of failure, in the case of anomalous thoracic duct, was there. Recent studies have shown successful identification of the thoracic duct with a near‐infrared imaging system by preoperative injection of indocyanine green dye in inguinal nodes under the guidance of ultrasound 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of our case study was that the anatomy of the thoracic duct before surgery was not studied due to a lack of lymphangiography. As the thoracic duct is known for frequent variation, 9 the chance of failure, in the case of anomalous thoracic duct, was there. Recent studies have shown successful identification of the thoracic duct with a near‐infrared imaging system by preoperative injection of indocyanine green dye in inguinal nodes under the guidance of ultrasound 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound has many advantages in contrast to other imaging modalities that are particularly important in children. It is fast, non-invasive, avoids ionizing radiation and sedation, provides excellent spatial resolution and offer the advantage of real time imaging at bedside (59). Especially in small children acoustic windows are much better and may widen application of this technique in the future like preoperative screening for lymphatic susceptibility or helping in guiding during invasive procedures.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Грудной проток (ГП) как главный коллектор лимфы у человека и млекопитающих животных давно привлекает к себе внимание и неоднократно становился объектом для исследований [1,2]. Не уменьшается интерес к его морфо-функциональным особенностям и сейчас [3,4,5,6,7,8]. Большое внимание уделяется ГП и в современной хирургии, особенно торакальной [9,10,11].…”
Section: Introductionunclassified